(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
The present study was undertaken to assess and evaluate the effect of two parameters on tablet formulation of Ciprofloxacin: a) particle size of raw material and b) storage conditions of both raw material and finished product. The raw materials were two commercial products, coarse (RM1) and fine (RM2) and locally produced granular form (RM3) prepared from RM2. Three tablet formulations were prepared from the raw materials and designated as F1, F2 and F3. The formulation F1 were prepared from RM1, F2 from RM2 by slugging and F3 from RM3 by direct compression. The raw materials and finished products were then subjected to assessment of the different parameters at the time of production and after storage for three month. The particle size distribution for the raw materials was found to be < 100, 100 – 250 and > 250 μm for RM2, RM1 and RM3, respectively. The moisture uptake at 25°C and 4°C under 75% RH was found to be the highest for the fine powder raw material (RM2), however, the developed granular form RM3 showed the least uptake. Moreover, F2 did not attain 80% dissolution after storage of 3 month. The F1 and F3 formulation passed the dissolution test after storage of 3 month, hence, F3 showed the highest value of dissolution (82%) in 30 minutes. The physicochemical properties of raw materials, storage conditions, and manufacturing techniques were found to exert a great influence over the dissolution behavior of Ciprofloxacin tablet formulations. Key words: Ciprofloxacin tablets; dissolution behavior; physicochemical properties; storage conditions DOI: 10.3329/sjps.v2i2.5819 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 8-15